2002
DOI: 10.1046/j.1365-3156.2002.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Brugia timori and Wuchereria bancrofti infections in Indonesia using DEC or a combination of DEC and albendazole: adverse reactions and short‐term effects on microfilariae

Abstract: SummaryFilariasis caused by Brugia timori and Wuchereria bancrofti is an important public health problem on Alor island, East Nusa Tenggara, Indonesia. To implement a control programme, adverse reactions and short-term effects on the microfilaria (mf) density were studied following a divided dose of diethylcarbamazine (DEC, 6 mg/kg body weight -100 mg on day 1 and the rest on day 3) or a single dose of DEC (6 mg/kg body weight on day 3) and albendazole (Alb, 400 mg). In order to define the most appropriate reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…Cooper et al (17) have also previously reported evidence suggesting that high levels of RANTES in plasma were able to down-regulate eosinophil sequestration. Severe allergic reactions to praziquantel treatment of schistosomiasis are not as frequent as they are following treatment of filariasis, in which such reactions are significantly associated with microfilaria density and fluctuations in circulating eosinophil numbers (4,16,61). Bronchial allergen provocation studies have also shown a close association between eosinophil counts and postchallenge eosinophil fluctuations and the development and magnitude of early and late asthmatic responses (15,20,68).…”
Section: Discussionmentioning
confidence: 99%
“…Cooper et al (17) have also previously reported evidence suggesting that high levels of RANTES in plasma were able to down-regulate eosinophil sequestration. Severe allergic reactions to praziquantel treatment of schistosomiasis are not as frequent as they are following treatment of filariasis, in which such reactions are significantly associated with microfilaria density and fluctuations in circulating eosinophil numbers (4,16,61). Bronchial allergen provocation studies have also shown a close association between eosinophil counts and postchallenge eosinophil fluctuations and the development and magnitude of early and late asthmatic responses (15,20,68).…”
Section: Discussionmentioning
confidence: 99%
“…Em países como a Indonésia, onde a prevalência da infecção por helmintos intestinais é bastante alta, o uso da combinação dietilcarbamazina vs albendazol, no programa de controle da filariose linfática levou a um impacto adicional no programa de controle de helmintos intestinais. 30 Dessa forma, os resultados aqui apresentados confirmam a associação de geohelmintos e filariose linfática o que deve levar as Secretarias de Saude da Região Metropolitana do Recife, junto com o Ministério da Saúde a rediscutir a associação do albendazol com dietilcarbamazina em áreas a serem implantadas o tratamento coletivo, como uma estratégia integrada de enfrentamento das duas endemias.…”
Section: Discussionunclassified
“…Although Indonesia has a long history in filariasis control programmes [12], filariasis is still in many areas a large public health problem and the new strategy recommended by GPELF was never evaluated. Therefore, studies were initiated to investigate the efficacy of a single dose DEC combined with alb to control W. bancrofti and B. timori infections on Alor island [13]. The treatment was judged to be efficient and safe enough to be employed in an MDA approach and an area endemic for B. timori was selected for annual follow-up studies [13-15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies were initiated to investigate the efficacy of a single dose DEC combined with alb to control W. bancrofti and B. timori infections on Alor island [13]. The treatment was judged to be efficient and safe enough to be employed in an MDA approach and an area endemic for B. timori was selected for annual follow-up studies [13-15]. …”
Section: Introductionmentioning
confidence: 99%